DOP057 ECCO-EBMT joint paper: autologous haematopoietic stem cell transplantation (AHSCT) in severe Crohn's disease: Summary of the ECCO-EBMT joint review. (16th January 2018) - Snowden, J; Panes, J; Alexander, T; Allez, M; Ardizzone, S; Dierickx, D; Finke, J; Hasselblatt, P; Hawkey, C; Kazmi, M; Lindsay, J; Onida, F; et al.
Abstract: Background: Despite recent progress in the treatment of Crohn's disease (CD), there is a subset of patients in whom the disease runs an aggressive course with progressive tissue damage requiring early and repeated surgical management. Increasing evidence, including the secondary endpoints of the "ASTIC" trial, 1, 2 supports sustained and profound improvement in gastrointestinal parameters and quality of life following high-dose immunosuppressive therapy and autologous haematopoietic stem cell transplantation (AHSCT) compared with standard therapy in this group of patients. International transplant registry data reflect the use of AHSCT in CD outside of trials in selected patients. As of September 2017, there have been a total of 172 transplant registrations of CD within the European Society for Blood and Marrow Transplantation (EBMT) registry, with 164 for autologous transplant procedures. However, AHSCT may be associated with significant treatment-related complications with risk of transplant-related mortality. Methods: In a joint initiative, the European Crohn's and Colitis Organisation (ECCO) and the EBMT have produced a consensus review summarising the rationale, evaluation, patient selection, along with evidence-based protocols for stem cell mobilisation and transplant procedures and systematic long-term follow-up. Results: Given the unique spectrum of issues, including technical aspects and inherent risks, we recommend that AHSCT should only be performed in experienced centres with expertise in both haematological and gastroenterological aspects of the procedure. Close co-operation between haematology and gastroenterology is needed at national and international levels. Accredited centres of specialisation and experience are required to bring AHSCT into clinical practice alongside modern biological treatments. In tandem, basic scientific studies, clinical trials and health economic evaluations should be conducted. Where possible patients should be treated on clinical trials and reporting of data to the EBMT registry is mandatory. Conclusions: This landmark ECCO and EBMT collaboration provides a basis for future development of AHSCT for this "difficult to treat" group of CD patients. 3 References: 1. Hawkey CJ, et al . Autologous hematopoetic stem cell transplantation for refractory Crohn disease: a randomized clinical trial. JAMA 2015;314:2524–34. 2. Lindsay JO, et al . Autologous stem-cell transplantation in treatment-refractory Crohn's disease: an analysis of pooled data from the ASTIC trial. Lancet Gastroenterol Hepatol, 2017;2:399–406. 3. Snowden JA, Panés Ji. Autologous haematopoietic stem cell transplantation (AHSCT) in severe Crohn's disease: a review on behalf of ECCO and EBMT. J. Crohns Colitis ; 2018; in press (open access).